Identification of the physical controls on the deposition of Aptian and Albian deep water sands in the Bredasdorp Basin, South Africa - Van Rensburg, Tamsyn (Department of Geological Sciences, 2017)
In the petroleum industry, the location of a new well is selected based on several factors, one of which is the presence of reservoir-quality sands. To determine the lateral extent of these sands away from well control, the depositional environment and character of the deposit must be adequately identified. This study aims to explain the physical controls on the deposition of the 13A (Aptian) and 14A (Albian) sequence sands within the deep water region of the Central Bredasdorp Basin through identifying the mass transport facies and processes and relating these to tectono-eustatic factors. Since a primarily seismic-based approach was used to achieve the project objective, the results reflect findings based on 3D seismic data interpretations as well as seismic surface and volume attribute extraction supported by wireline well logs and well completion reports. This dataset contains information that enabled the identification of the structural and stratigraphic architecture of the 13A and 14A sequences as a whole, the location of the sediment provenances and possible triggers of the mass flows as well as the consequential sand distribution trends from the basin slopes to across the basin floor during the Aptian-Albian time. The onshore Tankwa Basin was studied as an analogue to the Bredasdorp Basin because it hosts world class outcrops of deep water lowstand fan deposits and therefore shows the finer-scale details of the associated depositional stratigraphy. The 13A and 14A sequence sands would have entered the Bredasdorp Basin in progradational pulses alternating with mud-rich successions associated with local sea level fluctuations that were on trend with the gradual global sea level rise from the Aptian to the Albian. These alternating successions are identified as lowstand, transgressive and highstand systems tracts in the seismic and wireline well log data used in this study. The presented depositional model of the 13A sequence sands is a system of northwest to southeast sediment transport across the Central Bredasdorp Basin with indications of a final swing in orientation towards the east. The sands were mainly sourced from the paleo shelf edge on the northwest margin, although additional sediment input may have come from the west too. The faults that were active before and during the deposition of the Aptian-aged (13A) sands appear to have been the main control on sand distribution across the basin, guiding the sands from slope channels into basin floor fans and from shelf edge slumps into base of slope fans in a basinwide northwestsoutheast trend. The model of deposition of the 14A sequence sands is based on a channelised flow of sediment from the Central Bredasdorp Basin paleo shelf edge, down the slope and onto the basin floor primarily from the onshore source on the western margin. Supplementary sediment input may have originated from the Agulhas basement high on the southern margin of the basin in the form of less confined channels and mass wasting deposits. Inherited topography of the sea floor at the Albian time appears to have been the primary control on 14A sand distribution, causing bypass zones and giving rise to narrow, confined channel complexes despite some of the active faults possibly redirecting some of the sands from their initial trend. Overall the pattern of deposition of the Aptian and Albian deep water sands in the Bredasdorp Basin appears to have been physically controlled by the regional paleo seabed topography and fault activity until the late Aptian.